Species-specific genomic sequences for classification of bacteria. (August 2020) - Paul, Bobby; Kavia Raj, K.; Murali, Thokur Sreepathy; Satyamoorthy, K.
Abstract: Modern bacterial classification relies on genomic relatedness. Genetic variation in bacterial populations present a big challenge for taxonomic classification and recently several bacterial species have been reclassified based on the intra-species genome comparison. These were facilitated by next generation sequencing technologies and advances in genome comparison approaches which led to the rearrangement of diverse bacterial species and revolution in the microbial classification system. One of the outcome of these studies is the development of suitable DNA barcodes as reliable and cost-effective method for identifying various bacterial genera. Towards refining this further, we have applied a genome comparison approach in 1104 bacterial genome assemblies (excluding plasmids) to identify unique genomic segments among intra-species genome assemblies. Using extensive bioinformatics analysis, we have identified species-specific genomic regions and designed unique primers for 100 different species (belonging to 62 genera) which includes 62 pathogenic and 13 opportunistic pathogenic bacterial species and built a database (http://slsdb.manipal.edu/bact/ ). These species-specific genomic regions will have a major impact on in silico and molecular methods aimed at bacterial classification and identification. These may also serve as better DNA barcodes than the markers currently used for delineation of bacteria and may also find application in various translational research programs.